Treatment with a novel oleic-acid-dihydroxyamphetamine conjugation ameliorates non-alcoholic fatty liver disease in obese Zucker rats - Juan M. Decara; Francisco Javier Pavón; Juan Suárez; Miguel Romero-Cuevas; Elena Baixeras; Mariam Vázquez; Patricia Rivera; Ana L. Gavito; Bruno Almeida; Jesús Joglar; Rafael de la Torre; Fernando Rodríguez de Fonseca; et al. (The Company of Biologists, 2015)
Fatty liver disease is one of the main hepatic complications associated with obesity. To date, there are no effective treatments for this pathology apart from the use of classical fibrates. In this study, we have characterized the in vivo effects of a novel conjugation of oleic acid with an amphetamine derivative (OLHHA) in an animal model of genetic obesity. Lean and obese Zucker rats received a daily intraperitoneal administration of OLHHA (5 mg kg−1) for 15 days. Plasma and liver samples were collected for the biochemical and molecular biological analyses, including both immunohistochemical and histological studies. The expression of key enzymes and proteins that are involved in lipid metabolism and energy homeostasis was evaluated in the liver samples. The potential of OLHHA to produce adverse drug reactions or toxicity was also evaluated through the monitoring of interactions with hERG channel and liver cytochrome. We found that OLHHA is a drug with a safe pharmacological profile. Treatment for 15 days with OLHHA reduced the liver fat content and plasma triglyceride levels, and this was accompanied by a general improvement in the profile of plasma parameters related to liver damage in the obese rats. A decrease in fat accumulation in the liver was confirmed using histological staining. Additionally, OLHHA was observed to exert anti-apoptotic effects. This hepatoprotective activity in obese rats was associated with an increase in the mRNA and protein expression of the cannabinoid type 1 receptor and a decrease in the expression of the lipogenic enzymes FAS and HMGCR primarily. However, changes in the mRNA expression of certain proteins were not associated with changes in the protein expression (i.e. L-FABP and INSIG2). The present results demonstrate that OLHHA is a potential anti-steatotic drug that ameliorates the obesity-associated fatty liver and suggest the potential use of this new drug for the treatment of non-alcoholic fatty liver disease.